Improving the efficiency of adsorption filters with a short diffuser by improving their flow part - A. S. Korneeva; N. Yu. Filkin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The study examines short-diffuser adsorption filters designed to remove pollutants from vapor-gas mixtures. The design process of the flow path of such filters is considered, which includes the stages of determining the parameters of the adsorbent layer, modeling gas-dynamic processes using numerical methods in the ANSYS CFX program and analyzing the results. The numerical studies cover various options for backfilling the adsorbent, including layer profiling and the use of adsorbent with different porosity, which allows us to assess the impact of these factors on the aerodynamic resistance and overall efficiency of the filter. A design algorithm is also proposed that ensures optimal compliance between the adsorbent layer thickness and the local flow velocity, which helps to increase the protective action time of the filter and improve the quality of cleaning.